Fatty acid profiles in muscle of large yellow croakers (Larimichthys crocea) can be used to distinguish between the samples of Dai-qu stock and Min-yuedong stock. (April 2018) - Shen, Xi-Quan; Yan, Xiao-Jun; Xu, Ji-Lin
Abstract: Large yellow croaker ( Larimichthys crocea ) is a type of economic marine fishes mainly living in coastal area of China. In the present study, we investigated the fatty acid (FA) compositions in the muscles of Dai-qu stock and Min-yuedong stock large yellow croakers using gas chromatography-mass spectrometry (GC-MS). The results showed that the contents of some FAs were quite different between these two populations. Therefore, the FA composition could be used as a potential indicator for the identification of Dai-qu stock and Min-yuedong stock large yellow croakers. Specifically, the large yellow croakers with the FA ratios of [C18:1/(C20:1 + C22:1)]>5.0 and/or C20:5/C20:4 < 4.0 could be classified to Min-yuedong stock, while those with the FA ratios of [C18:1/(C20:1 + C22:1)] <5.0 and/or C20:5/C20:4 > 4.0 were classified to Dai-qu stock. The differences in the FA ratio between Dai-qu stock and Min-yuedong stock could be attributed to their primitive parents, which live in different sea areas with different temperatures. The cold-resistant genes in Dai-qu stock could be used as promising indicators for natural selection in the low-temperature environment, which mainly contributed to the differences of biochemical substances between Dai-qu stock and Min-yuedong stock. Highlights: A method to identify Dai-qu stock and Min-yuedong stock is developed. The fatty acid profiles in muscle were analyzed by GC-MS. The contents of C18:1n-9, C22:1n-9, C20:1n-9, C20:5n-3 and C20:4n-6 were quite different. When [C18:1/(C20:1 + C22:1)]>5.0 and/or C20:5/C20:4 < 4.0, it belongs to Min-yuedong stock. When [C18:1/(C20:1 + C22:1)] <5.0 and/or C20:5/C20:4 > 4.0, it belongs to Dai-qu stock.